Liver fibrosis increases the risk of subclinical atherosclerosis in patients with MASLD: a cross-sectional and longitudinal study - Haoyu Zhang; Fei Lin; Mengyuan Miao; Chengxiao Yu; Wen Guo (Nutrition & Metabolism)
Abstract Background This study investigated the associations between both the progression and regression of liver fibrosis and subclinical atherosclerosis in patients withmetabolic dysfunction-associated steatotic liver disease (MASLD). Methods We conducted a cross-sectional analysis of 5,633MASLD participants who underwent transient elastography and carotid ultrasonography (Stage I). Additionally, a longitudinal study followed 2,670MASLD individuals without carotid atherosclerosis (CAS) at baseline, who underwent at least two health check-up examinations (Stage II). We used CAS and brachial ankle pulse wave velocity (baPWV) as markers of subclinical atherosclerosis and calculated the noninvasive fibrosis index FIB-4 to evaluate the probability of fibrosis. Results In Stage I study, liver fibrosis was associated with increased CAS risk (OR = 1.17, 95%CI1.01–1.37, P = 0.045) and elevated baPWV (OR = 1.49, 95%CI 1.06–2.09, P = 0.022). In Stage II study, during a median of 24 months of follow-up, 466 (17.45%)MASLD patients developed CAS. Compared to patients with stable low probability, those who progressed to a high-intermediate probability of advanced fibrosis had a higher risk of incident CAS (HR = 1.89, 95%CI1.42–2.51, P < 0.001). In addition, persistent high-intermediate probability and regression to low probability of advanced fibrosis were associated with 2.32-fold (95%CI 1.86–2.89, P < 0.001) and 1.82-fold (95% 1.22–2.71, P = 0.004) increased risk of incident CAS, respectively. Moreover, persistent high-intermediate probability was independently correlated with elevated baPWV risk (HR = 3.17, 95%CI 1.76–5.71, P < 0.001). Conclusions Persistent or progression to high-intermediate probability of fibrosis was associated with an increased risk of subclinical atherosclerosis, while regression to low probability of fibrosis does not significantly reduce this risk.